A virtualização de processo com o uso de mundos virtuais: um estudo do processo ensino-aprendizagem a partir da perspectiva dos participantes do processo - Noveli, Márcio (2013)
Information and Communication Technologies (ICT) have allowed that, in the organizational context, processes which depended on the physical presence of those involved, individuals or objects, at the same place and time, occur without these limits. The explanation for this phenomenon has gone through several models and theories, based on different areas and from different levels of analysis, following the evolution of the capabilities of these technologies over the years, including in the area of Information Systems (IS). From this area, specifically from the group of studies which assumes that processes become virtual when the ICT used to enable them are adopted/used by individuals involved in the process, this research was delimited to an empirical study on the divergence about the adequacy of virtual worlds in teaching-learning process virtualization, starting from a general model based on the Process Virtualization Theory (PVT), aiming to identify the relationship between the requirements of a process and the capabilities of ICTs in a process virtualization. Thus, it was used the multiple case studies strategy, which included 3 cases and various sources of evidence, allowing, through techniques of content analysis: (1) identify five constructs which stood out as requirements of the teachinglearning process , including an additional construct to the PVT model, two capabilities of this technology, three indicators of virtualization, plus three other factors that were present in this process, (2) describe them as to how they were evaluated and (3) map how they were associated, from the perspective of the participants in the process. It also identified a systematic framework of relations between the factors identified and evaluated, which indicates that ICT capabilities are related to the filling of the process requirements, enabling virtualization, and other factors identified are involved in process virtualization.